Can immigrants help women "have it all"? Immigrant labor and women's joint fertility and labor supply decisions - Delia Furtado (IZA Journal of Migration, 2015)
This paper explores how inflows of low-skilled immigrants impact the tradeoffs women face when making joint fertility and labor supply decisions. I find increases in fertility and decreases in labor force participation rates among high-skilled US-born women in cities that have experienced larger immigrant inflows. Most interestingly, these changes have been accompanied by decreases in the strength of the negative correlation between childbearing and labor force participation, an often-used measure of the difficulty with which women combine motherhood and labor market work. Using a structured statistical model, I show that the immigrant-induced attenuation of this negative correlation can explain about 24% of the immigrant-induced increases in the joint likelihood of childbearing and labor force participation in the US between the years 1980 and 2000.
Keywords: D10; F22; J13; J22; R23; 330; Child care; Fertility; Labor force participation; Immigration; Tetrachoric correlation